Investigating the Development of Individuals with Mental and Physical Problems Receiving Water Therapy in a Special Education and Rehabilitation Center - Ahmet Şirinkan (Journal of Educational Issues, 2024)
Investigation of the physical and psychological development challenged individuals receiving water therapy in a private education rehabilitation center. The aim of this study is to investigate the physical and psychological development challenged individuals receiving water therapy in a private education rehabilitation center. 5 children with mentally and physically problems who took water therapy in the Special Education Rehabilitation Center participated in the study. Children aged between 3-8. Children who have mentally problematic, who have participated in the research, have severe, moderate and mild mental problems and who have problems physically also have placenta, quatri plaque, spina bifida etc. children with orthopedic insufficiency. Special mobility training program was prepared for the children to be able to make joint problems for children with mental problems and physical problems. While the program was being prepared, support was received from special educator, water therapist and repertoire people. The study was administered 4 months, 2 days a week and 60-90 minutes. At the beginning of the research, the children who had mental problems were afraid of entering the water, they did not comply with the commands, they did not want to be separated from the mother and father. At the end of the research process, children with mental problems enter the water comfortably and even hurry to enter, they are not afraid of water, they are more adaptable to the commands, they continue to work separately from their parents, they are more willing to enter the water in children who have problems with orthopedic problems. It was observed that most of the children who wanted to move in the water, they were mostly able to perform the movements, and the majority of the children (90%) who had walking pants had walking exercises.